2022
DOI: 10.1016/j.jdsr.2021.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and primary evidence of silver diamine fluoride on root caries management

Abstract: Root caries is a growing problem for the worldwide aging population. Silver diamine fluoride (SDF) contains high concentrations of silver and fluoride ions, which prevents and arrests root caries, as well as dentin caries in the primary teeth of young children. Unlike other fluoride products that mainly reduce the formation of new carious lesions, 38% SDF is an effective agent that can efficiently arrest the carious process, remineralize the decayed dental tissues, and protect the tooth structure against the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…Thus, the combination of CPC and GO ultrathin film is likely a clinically significant method for addressing dental disease. The silver diamine fluoride coating method (silver deposited on the tooth surface) is currently used to prevent dental caries, but the silver coating causes darkening of the teeth, which is problematic from an esthetic standpoint 33 . GO/CSAA is transparent and does not alter the color of teeth, so satisfying esthetic requirements.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the combination of CPC and GO ultrathin film is likely a clinically significant method for addressing dental disease. The silver diamine fluoride coating method (silver deposited on the tooth surface) is currently used to prevent dental caries, but the silver coating causes darkening of the teeth, which is problematic from an esthetic standpoint 33 . GO/CSAA is transparent and does not alter the color of teeth, so satisfying esthetic requirements.…”
Section: Resultsmentioning
confidence: 99%
“…To arrest residual caries and enhance remineralization in deep carious lesions managed by partial caries removal, ozone and silver diamine fluoride treatments were suggested [ 35 , 36 , 37 ]. Further studies are needed to confirm procedural effectiveness, any adverse effects on bonding, biocompatibility, or deep penetration, and esthetic consequences [ 38 ].…”
Section: Minimal Invasive Management Of Deep Caries and The Fate Of R...mentioning
confidence: 99%
“…An umbrella review, summarizing systematic reviews on the effectiveness of silver diamine fluoride, reported consistent support for its effectiveness in arresting coronal caries in the primary dentition as well as arresting and preventing root caries in older adults 169 . A protocol has been proposed for use of silver diamine fluoride for root caries where the solution is applied and then a few days or a week later a second treatment is applied 170 . The rationale for the two‐appointment protocol is that the carious dentin will become very dark after a few days, making it easier to distinguish between carious and sound dentin, a process that helps prevent the removal of excess tooth structure should a restoration subsequently be placed for esthetic reasons 170 …”
Section: Conservative Treatment When Caries Are Present In Cervical L...mentioning
confidence: 99%
“…169 A protocol has been proposed for use of silver diamine fluoride for root caries where the solution is applied and then a few days or a week later a second treatment is applied. 170 The rationale for the two-appointment protocol is that the carious dentin will become very dark after a few days, making it easier to distinguish between carious and sound dentin, a process that helps prevent the removal of excess tooth structure should a restoration subsequently be placed for esthetic reasons. 170 The primary author of this publication has effectively used silver diamine fluoride to arrest cervical caries in adults while recognizing there will be substantial darkening of the area following treatment (Fig 16).…”
Section: Conservative Treatment When Caries Are Present In Cervical L...mentioning
confidence: 99%